Kajian Dalalah dalam Perspektif Relasi Kesalingan Suami Istri Menurut Konsep Keluarga Maslahah Nahdlatul Ulama - Husna, Khotimatul (DIKTUM: Jurnal Syariah dan Hukum, 2022)
In understanding the texts to carry out legal istinbat (decisions/legal conclusions), mujtahids do not only pay attention to what is written in the explicit sentence structure, but also pay attention to what is implied by the text, namely the meaning contained through signs and dalalah (hint) nash. The ushul fiqh scholars have differences in determining the distribution, levels, and methods for using this dalalah. However, this paper will only limit the opinion of Hanafiah scholars. The text's instructions (dalalah) need to be understood contextually regarding the relationship between husband and wife in the family, so that understanding the text can be a solution to contemporary family problems. This paper will examine dalalah with a new theoretical approach called qiraah mubadalah that was coined by Faqihuddin Abdul Kodir in the interdependence of husband and wife according to the concept of the Nahdlatul Ulama maslahah family.